Biotransformation, metabolic response, and toxicity of UV-234 and UV-326 in larval zebrafish (Danio rerio). (April 2023) - Zhang, Jiye; Huang, Ying; Pei, Youjun; Wang, Yuyang; Li, Mingwan; Chen, Huihui; Liang, Xuefang; Martyniuk, Christopher J.
Graphical abstract: Highlights: UV-234 and UV-326 showed different bioaccumulation capacity and biotransformation. Both BUVSs activated antioxidant defense system but inhibited lipid metabolism. Metabolomic changes induced by BUVSs converged to cGMP-PKG pathway. BUVSs have comparable toxicity in inducing apoptosis and neuroinflammation. Abstract: Benzotriazole ultraviolet stabilizers (BUVSs) are emerging pollutants that are widely detected in aquatic ecosystems. While structure-dependent effects of BUVSs are reported, the relationship between biotransformation and toxicity outcomes remains unclear. In this study, zebrafish embryos were exposed to two common BUVSs (UV-234 and UV-326) at 1, 10, and 100 µg/L for up to 7 days. Comparison of their uptake and biotransformation revealed that the bioaccumulation capacity of UV-234 was higher than that of UV-326, while UV-326 was more extensively biotransformed with additional conjugation reactions. However, UV-326 showed low metabolism due to inhibited phase II enzymes, which may result in the comparable internal concentrations of both BUVSs in larval zebrafish. Both BUVSs induced oxidative stress while decreased MDA, suggesting the disturbance of lipid metabolism. The subsequent metabolomic profiling revealed that UV-234 and UV-326 exerted different effects on arachidonic acid, lipid, and energy metabolism. However, both BUVSs negatively impacted the cyclic guanosine monophosphate / protein kinase G pathway. This converged metabolic change resulted in comparable toxicity of UV-234 and UV-326, which was confirmed by the induction of downstream apoptosis, neuroinflammation, and abnormal locomotion behavior. These data have important implications for understanding the metabolism, disposition, and toxicology of BUVSs in aquatic organisms.